Effectiveness of seed priming techniques for small grain cereals - Nedoborenko, Yu.; Sakhno, T. (Scientific Progress & Innovations, 2025)
This review aims to consolidate existing scientific insights regarding seed priming techniques for small grain cereals, perform a bibliometric assessment of scholarly activity in this area, and substantiate the urgency of intensifying research efforts to promote sustainable agricultural practices. Small grain cereals are vital contributors to global food systems and play an important role in restoring soil health. Pre-sowing seed treatment approaches for these crops are indispensable, as they support not only enhanced productivity but also contribute to environmental sustainability and the preservation of biodiversity. The agroecological relevance of seed priming technologies for small grain cereals is particularly high due to several key factors. Seed priming is a pre-sowing treatment technique that induces a physiological state in seeds, enhancing seedling survival and promoting more efficient germination. Various types of seed priming exist, including hydropriming, halopriming, osmopriming, biopriming, hormone priming, chemopriming, thermopriming, solid matrix priming, nanopriming, and physical methods. Despite its long-standing history and practical importance, seed priming remains underdeveloped and underutilized. The body of scientific literature on seed priming is relatively limited. To better understand the patterns observed in seed priming research over the past twenty-four years, a bibliometric analysis was conducted using the ScienceDirect database and compared with similar analyses conducted by other researchers using the Science Citation Index Expanded (SCI-E). The results indicate that seed priming research is significantly constrained in terms of volume, quantity, and quality. Therefore, advancing scientific research and fostering collaboration in this domain is crucial. Such progress requires both financial support and improved coordination among researchers with diverse expertise and perspectives.